2011
DOI: 10.14236/ewic/hci2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reflection on Personal Values to support Value-Sensitive Design

Abstract: The impact of ubiquitous technology and social media on our lives is rapidly increasing. We explicitly need to consider personal values affected or violated by these systems. Value-sensitive design can guide a designer in building systems that account for human values. However, the framework lacks clear steps to guide elicitation of stakeholders' values. We argue that developing tools for value elicitation that designers can use or give to stakeholders is a feasible solution to this challenge. Crucial in elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…No que diz respeito à gestão de processos de desenvolvimento, Barn et al (2015b), Barn e Barn (2016), Greef et al (2013), Pommeranz et al (2011) e Weigand (2019 apresentam suas pesquisas para tentar melhorar esses processos, Thinyane e Goldkind ( 2020 Há diversos benefícios advindos do DSV, pois se trata de uma abordagem que está presente em vários cenários que contemplam a humanidade e a tecnologia, como pode ser visto na nuvem de palavras da Figura 2.…”
Section: Como O Design Sensível a Valores Tem Sido Adotado Pela Compu...unclassified
See 1 more Smart Citation
“…No que diz respeito à gestão de processos de desenvolvimento, Barn et al (2015b), Barn e Barn (2016), Greef et al (2013), Pommeranz et al (2011) e Weigand (2019 apresentam suas pesquisas para tentar melhorar esses processos, Thinyane e Goldkind ( 2020 Há diversos benefícios advindos do DSV, pois se trata de uma abordagem que está presente em vários cenários que contemplam a humanidade e a tecnologia, como pode ser visto na nuvem de palavras da Figura 2.…”
Section: Como O Design Sensível a Valores Tem Sido Adotado Pela Compu...unclassified
“…Tuomela et al (2019) colaboram mostrando a influência direta dos stakeholders e concluem dizendo que ao desenvolver design de casas inteligentes, os indivíduos que devem ter prioridade são os que vão morar nas casas. Pommeranz et al (2011) e Battistuzzi et al (2018) enfatizam que usar DSV nos estágios iniciais de um projeto pode trazer requisitos ainda mais específicos e melhorar a fase de desenvolvimento do produto. Dadgar e Joshi (2015), Barn et al (2015a) Por mais que seja possível identificar contribuições do DSV, alguns autores encontraram algumas dificuldades na implementação do mesmo, conforme pode ser observado na Figura 3.…”
Section: Como O Design Sensível a Valores Tem Sido Adotado Pela Compu...unclassified
“…Personally-collected data (about an aspect of a young person's life like their mood, exercise or productivity) can offer just such a boundary object [7; 21]. Some related work has shown that such learning can extend to adolescents' identity formation, prompting reflection about life goals [33], values [22] and socio-political context [31] through constructing narratives about personal data.…”
Section: Social and Emotional Learningmentioning
confidence: 99%
“…Although some publications explicitly stated that personal informatics systems should respect privacy (e.g., [49,194,224,225]), only 36% of papers (187) explicitly mentioned ethical or privacy concerns. 69 of those (37%) referred to concerns broadly, typically mentioning that privacy is an important consideration for future systems or future study.…”
Section: Privacy and Ethical Challengesmentioning
confidence: 99%